2019
DOI: 10.1155/2019/7387601
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Local Injection of RAGE-Aptamer Suppresses the Growth of Malignant Melanoma in Nude Mice

Abstract: Accumulating evidence has suggested the pathological role of advanced glycation end products (AGEs) and their receptor RAGE axis in aging-associated disorders, including cancers. In this study, we examined the effects of local injection of RAGE-aptamer adjacent to the tumor on G361 melanoma growth in nude mice. We further investigated the effects of RAGE-aptamer on oxidative stress generation, RAGE, vascular endothelial growth factor (VEGF), and monocyte chemoattractant protein-1 (MCP-1) gene expression in Nε-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 40 publications
0
9
0
Order By: Relevance
“…We have previously shown that AGEs stimulate growth and VEGF expression in both endothelial cells and malignant melanoma cells by inducing the ROS generation through the interaction with RAGE (29,43). Oxidative stress and redox-sensitive transcriptional factor are involved in VEGF and MMP-9 gene expression in various kinds of cells, including tumor cells (29,(43)(44)(45)(46). Moreover, p66ShcA has recently been shown to play a role in breast cancer metastasis, while quercetin, an anti-oxidant suppresses the mobility as well as VEGF and MMP-9 expression of breast cancer cells (47,48).…”
Section: Discussionmentioning
confidence: 99%
“…We have previously shown that AGEs stimulate growth and VEGF expression in both endothelial cells and malignant melanoma cells by inducing the ROS generation through the interaction with RAGE (29,43). Oxidative stress and redox-sensitive transcriptional factor are involved in VEGF and MMP-9 gene expression in various kinds of cells, including tumor cells (29,(43)(44)(45)(46). Moreover, p66ShcA has recently been shown to play a role in breast cancer metastasis, while quercetin, an anti-oxidant suppresses the mobility as well as VEGF and MMP-9 expression of breast cancer cells (47,48).…”
Section: Discussionmentioning
confidence: 99%
“…In the presence of RAGE-aptamer #1, the K d value exhibited two orders of magnitude higher level [ 16 ]. Since we have reported that RAGE-aptamer clone #1 did not exert nonspecific toxic effects in both cell culture and animal model systems [ 15 , 19 ], we used RAGE-aptamer clone #1 for the following experiments.…”
Section: Resultsmentioning
confidence: 99%
“…The specimen of kidneys and livers were fixed with 4% paraformaldehyde, embedded in paraffin, sectioned at 4 μ m intervals and mounted on glass slides. The sections were left in 0.3% hydrogen peroxide for 30 minutes to block endogenous peroxidase activity and incubated overnight at 4°C with primary antibodies, and the reactions were visualized with a Histofine Simple Stain Mouse MAX PO (MULTI) kit (Cat# 424152, Nichirei Bioscience Inc., Tokyo, Japan) as described before [ 19 ]. Ten images were captured per section from individual mice in each group.…”
Section: Methodsmentioning
confidence: 99%
“…The sections were incubated with monoclonal antibody raised against AGE 62 after pretreatment with blocking agents, and the reactions were visualized with a Mouse on Mouse Basic Kit (BMK-2202; Vector Laboratories, Burlingame, CA) 63 .…”
Section: Methodsmentioning
confidence: 99%